P68 Sexual health literacy and men who have sex with men (msm): a scoping review of research literature. (18th May 2015) - Martin, Susan; Young, Ingrid; Riddell, Julie; Hilton, Shona; McDaid, Lisa; Flowers, Paul; Gilbert, Mark
Abstract : Background: Health literacy is a priority for health policy. However, there is limited research on how health literacy influences sexual health, particularly among men who have sex with men (MSM). Aim: To review sexual health literacy research among MSM in high-resource countries (UK, Canada, USA, Australia). Methods: We searched relevant databases (MEDLINE, Embase, Health and Psychosocial Instruments, Web of Science) to identify research which examined sexual health literacy and MSM explicitly and implicitly (using formal and informal articulations of health literacy) along with a set of sexual health and MSM terms. Relevant articles were identified, coded and assessed to illustrate the range of evidence available. Results: We found no studies explicitly focusing on sexual health literacy, and three exploring health literacy. Findings highlight the need for tailored information, healthcare and promotion for different groups of MSM, variable health literacy levels, and the importance of social context. We found 611 articles that implicitly explored sexual health literacy. We analysed a sub-sample which focused on interactive health literacy (negotiating, applying knowledge and interaction). There was a strong focus on communication and negotiation (verbal, non-verbal and online) with sexual partners and health providers, and the varying contexts within which these interactions take place. Discussion: We found no research on explicit sexual health literacy with MSM. Clinic-based interventions could use health literacy as a tool to improve sexual health. Findings suggest that tailored health information, communication skills, and the role of social context in shaping sexual health literacy skills could play a critical role.